USAGE OF HEAVY METALS IN AYURVEDIC FORMULATIONS AND ITS MANAGEMENT: A REVIEW - Agarwal, *Princy; Rajat, Vaishnav; Anju, Goyal (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda is a comprehensive and systematic medicinal system, originated in India. It takes into consideration all aspects of health, including mental, physical and social components. According to the principles of Ayurvedic medication, heavy metals possess considerable therapeutic properties and can be administered to the patients after being processed properly as mentioned within the Rasashastra, in prescribed quantities. However, improper manufacturing processes might lead to higher levels of heavy metals remaining in the final product which may be dangerous. They may also be present as impurity rather than being added willfully. Heavy metals possess tendency to accumulate in vital organs and hence, pose a particular health risk. The presence of impurities in drug samples, whether herbal or pharmaceutical, is of great concern, not only because some contaminants are inherently toxic, but also they may negatively affect the stability of the drug and the lifespan, or they can cause unwanted side effects. The quality assurance of herbal formulations is the main concern of current phytomedical era due to the increase in toxicity reports. As a consequence, both organic and inorganic (elemental) impurities must be monitored and controlled in final dosage form starting from the raw materials itself. This article deals with the various aspects of heavy metals in Ayurvedic medicines such as their sources, methods used for their determination, their therapeutic significance, their toxic effects and also summarizes various guidelines and limits for their regulation.